The American Constitution and the debate over originalism - Goldford, Dennis J., 1948- (Cambridge University Press, 2005)
"Located at the intersection of law, political science, philosophy, and literary theory, this work of constitutional theory explores the nature of American constitutional interpretation through a reconsideration of the long-standing debate between the interpretive theories of originalism and nonoriginalism. It traces that debate to a particular set of premises about the nature of language, interpretation, and objectivity, premises that raise the specter of unconstrained, unstructured constitutional interpretation that has haunted contemporary constitutional theory. The book presents the novel argument that a critique of the underlying premises of originalism dissolves not just originalism but nonoriginalism as well, which leads to the recognition that constitutional interpretation is already and always structured."--Jacket